PENINGKATAN IKLIM USAHA KECIL MENENGAH MELALUI STRATEGI KOMUNIKASI DINAS PENANAMAN MODAL DAN PERIZINAN TERPADU SATU PINTU - Wahjoe Mawardiningsih, Ali Arif Setiawan & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2017)
Small and Medium Enterprises (SMEs) are of special concern to thegovernment. Reform and regional autonomy triggered the implementationand development of a new public service bureaucracy (NPS) into theadministration of public services. NPS places the citizens to be served. Onegovernment program is One Stop Service (OSS). OSS uses the principle ofwork easy, cheap, fast and can be transparent. Thus, the institutionconcerned makes communication strategy based on media strategy so thatpeople are more familiar and actively participate. This study aims to find outhow the implementation of the communication strategy, and how theeffectiveness of communication strategies to the public in Sragen regency.Data were collected by interviewing the resource persons involved in thecompilation and implementation of the communication strategy and bycollecting supporting data. The results show that DPMPTSP works togetherwith related SKPD, improvise to formulate and run socialization andpublication through media according to the typology of audience. DPMPTSPavoids high-cost media and further maximizes the potential of existingresources. As a mainstay for further development is the online media.Nevertheless DPMPTSP has succeeded in improvisation as evidenced bythe increase of applicants for permits and growth of SMEs.Keywords: SME, one stop service, government communication strategy